Subaltern Women, Colonialism, and Feminism in Remy Sylado’s Novel "Kembang Jepun" - Intan Sholeha; Suroso Suroso (JENTERA: Jurnal Kajian Sastra, 2026)
This study is motivated by the plight of subaltern women who have never been given the opportunity to speak out and lack a space to voice their experiences within an oppressive colonial structure. This study aims to analyze the struggles of subaltern women in Remy Sylado’s novel Kembang Jepun through James Scott’s (1990) concept of the “hidden transcript,” based on a postcolonial feminist approach. The concept of the hidden transcript was chosen because it can reveal the forms of subaltern women’s struggles that are not always carried out openly. The method used in this study is qualitative descriptive, with the novel Kembang Jepun by Remy Sylado as the data source. Data collection techniques involved careful and repeated reading, marking sentences that indicate subaltern women’s struggles, and recording data on subaltern women’s struggles into data cards. Data analysis in this study was conducted through data collection, data condensation, data presentation, and drawing conclusions. The findings of this study include women’s struggles through (1) elementary forms of disguise (3 data points), (2) breaking the silence (7 data points), and (3) breaking the charm (6 data points), totaling 16 data points. This study enriches feminist scholarship through Spivak’s concept of the subaltern, which can be interpreted through the hidden transcript perspective to understand the struggles of subaltern women within the context of colonial literature. Abstrak Penelitian dilatarbelakangi oleh permasalahan perempuan subaltern yang tidak pernah diberi kesempatan untuk bersuara dan tidak memiliki ruang untuk menyuarakan pengalamannya dalam struktur kolonial yang menindas. Penelitian ini bertujuan untuk menganalisis perjuangan subaltern perempuan dalam novel Kembang Jepun karya Remy Sylado melalui konsep hidden transcript James Scott (1990) berdasarkan pendekatan feminisme poskolonial. Konsep hidden transcript dipilih karena mampu mengungkap bentuk-bentuk perjuangan perempuan subaltern yang tidak selalu dilakukan secara terbuka. Metode dalam penelitian ini yakni deskriptif kualitatif dengan sumber data novel Kembang Jepun karya Remy Sylado. Teknik pengumpulan data dilakukan dengan cara membaca dengan teliti serta membaca secara berulang, memberi penanda pada kalimat yang menunjukkan perjuangan perempuan subaltern, mencatat data perjuangan perempuan subaltern ke dalam kartu data. Dalam penelitian ini dilakukan analisis data melalui pengumpulan data, kondensasi data, penyajian data, dan penarikan kesimpulan. Temuan penelitian ini meliputi perjuangan perempuan melalui (1) elementary forms of disguise, terdapat 3 data, (2) breaking the silence, terdapat 7 data, dan (3) breaking the charm, terdapat 6 data, dengan total 16 data. Penelitian ini memperkaya kajian feminisme melalui konsep subaltern Spivak yang dapat dibaca melalui perspektif hidden transcript untuk memahami perjuangan perempuan subaltern dalam konteks sastra kolonial.